Edukasi Pelatihan Sistem Penjurnalan Perusahaan Dagang untuk Siswa-Siswi SMA - Suhendah, Rousilita; Jennifer , Jennifer; Goh , Erica; Heni , Heni (Penerbit Goodwood, 2025)
Purpose: To improve knowledge and understanding of the trading company journaling system for Tarsisius High School students so that they can understand trading company journals and can make trading company financial reports. Methodology/approach: The community service team conducted the activities about trading company journaling systems by lecturing and strengthening materials by providing pre-test and post-test. Results/findings: the post-test results of Tarsisius 1 High School students showed an increase in understanding of the trading company journaling system material compared to the pre-test results. The post-test mean result showed 72.0 and the pre-test results were 61.3. This indicates Tarsisius 1 High School students can be understood by the training participants. Conclusions: The PKM team conducted a training on journalizing systems for trading companies at SMA Tarsisius 1 for grades X–XII. The students responded enthusiastically and showed improved understanding of accounting and cost of goods sold. The school expressed interest in continuing the program next year with topics on manufacturing accounting, including cost of production, job order, and process costing. Limitations: The number of participants who took part in the training activities was limited so that not all Tarsisius High School students received training because this activity had the same schedule as the sports and arts competitions at the school. Contribution: This Community Service activity is one of the activities to educate and transfer knowledge about the trading company journaling system to the community, especially for high school students so that they can make financial reports for trading companies.